Tumor Necrosis Factor and Schistosoma mansoni egg antigen omega-1 shape distinct aspects of the early egg-induced granulomatous response. - Kevin K Takaki; Francisco J Roca; Gabriele Schramm; Ruud H P Wilbers; Wannaporn Ittiprasert; Paul J Brindley; Gabriel Rinaldi; Matthew Berriman; Lalita Ramakrishnan; Antonio J Pagán (Public Library of Science (PLoS), 2021)
Infections by schistosomes result in granulomatous lesions around parasite eggs entrapped within the host tissues. The host and parasite determinants of the Schistosoma mansoni egg-induced granulomatous response are areas of active investigation. Some studies in mice implicate Tumor Necrosis Factor (TNF) produced in response to the infection whereas others fail to find a role for it. In addition, in the mouse model, the S. mansoni secreted egg antigen omega-1 is found to induce granulomas but the underlying mechanism remains unknown. We have recently developed the zebrafish larva as a model to study macrophage recruitment and granuloma formation in response to Schistosoma mansoni eggs. Here we use this model to investigate the mechanisms by which TNF and omega-1 shape the early granulomatous response. We find that TNF, specifically signaling through TNF receptor 1, is not required for macrophage recruitment to the egg and granuloma initiation but does mediate granuloma enlargement. In contrast, omega-1 mediates initial macrophage recruitment, with this chemotactic activity being dependent on its RNase activity. Our findings further the understanding of the role of these host- and parasite-derived factors and show that they impact distinct facets of the granulomatous response to the schistosome egg.